Is the Italian public debt really unsustainable? An historical comparison (1861-2010) - Silvana Bartoletto; Bruno Chiarini; Elisabetta Marzano (Center for Economic Studies and ifo Institute (CESifo), 2013)
The aim of this paper is to analyze the sustainability of public debt in Italy during the last 150 years (1861-2010) by employing a database containing several statistical novelties: new time series estimates of public debt and GDP (respectively Bank of Italy and Baffigi, 2011) and an original reconstruction of the revenues of the State. The key economic indicators analyzed include public debt, primary and total deficits, nominal and real GDP rates of growth. Long-term analysis of new homogeneous statistical series has led to a different perspective, in particular when compared with the existing Italian literature on the debt-to-GDP ratio. Two main issues are addressed. First, we examine the size and dynamics of public finance aggregates in a long-term perspective. In particular, we carry out a detailed historical analysis, aiming to identify the determinants of public debt and its ratio to GDP. Second, following the approach proposed both by Bohn (1998, 2005) and Doi et al. (2011), we test for the sustainability of public debt in Italy, comparing four different historical periods.
Keywords: C22; E62; H60; N13; N14; N23; N24; 330; public debt sustainability; Italian debt history; intertemporal budget constraint; fiscal rule